Modelling policies for urban sustainability - Kari Lautso; Klaus Spiekermann; Michael Wegener (European Regional Science Association (ERSA), 2002)
The objective of the EU research project PROPOLIS (Planning and Research of Policies for Land Use and Transport for Increasing Urban Sustainability) is to assess urban strategies and to demonstrate their long-term effect in European cities. To reach this goal, a comprehensive framework of methodologies including integrated land use, transport and environmental modelling as well as indicator, evaluation and presentation systems have been developed. Sustainable development is viewed as comprising the environmental, socio-cultural and economic dimension. About thirty key indicators have been defined to measure the three dimensions of sustainability, such as air pollution, consumption of natural resources, quality of open space, population exposure to air pollution and noise, equity and opportunities and economic benefits from transport and land use. Indicator values are derived from state-of-the-art urban land use and transport models. A number of additional modules, including a justice evaluation module, an economic evaluation module and a GIS-based raster module, have been developed and integrated to provide further indicator values. Both multicriteria and cost-benefit analysis methods are used to consistently evaluate the impact of the policies. The environmental and social dimensions of sustainability are measured using multicriteria analysis for the evaluation of the indicators, whereas cost-benefit analysis is used for the economic dimension. The modelling and evaluation system is currently being implemented in seven European urban agglomerations: Bilbao (Spain), Brussels (Belgium), Dortmund (Germany), Helsinki (Finland), Inverness (Scotland), Naples (Italy) and Vicenza (Italy). A large number of policies will be tested with the modelling and evaluation system in the seven urban regions. Policies to be investigated are land use policies, transport infrastructure policies, transport regulation and pricing policies and combinations of these. Besides a common policy set for all seven urban regions, city-specific local policies will be assessed as well. The first part of the paper will introduce the methodology and the modelling system developed. The second part will present first results of the policy testing and evaluation. The paper will conclude with initial conclusions on successful strategies to enhance the long-term sustainability of urban regions.
Keywords: 330